2011
DOI: 10.1063/1.3624331
|View full text |Cite
|
Sign up to set email alerts
|

Zigzag GaN/Ga2O3 heterogeneous nanowires: Synthesis, optical and gas sensing properties

Abstract: Zigzag GaN/Ga2O3 heterogeneous nanowires (NWs) were fabricated, and the optical properties and NO gas sensing ability of the NWs were investigated. We find that NWs are most effective at 850 °C at a switching process once every 10 min (on/off = 10 min per each) with a mixture flow of NH3 and Ar. The red shift of the optical bandgap (0.66 eV) is observed from the UV-vis spectrum as the GaN phase forms. The gas sensing characteristics of the developed sensor are significantly replaced to those of other types of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…These peak positions and spin-orbit splitting consistent with the previous literature confirm the synthesis of GaN. [25,32,33] O 1s CL spectra were also recorded to verify the presence of oxygen with Ga as shown in Figure S2, Supporting Information. It is observed that there was no chemical interaction between Ga and oxygen, suggesting the synthesis of GaN with the absence of any gallium oxy-nitride compound.…”
Section: Resultssupporting
confidence: 87%
“…These peak positions and spin-orbit splitting consistent with the previous literature confirm the synthesis of GaN. [25,32,33] O 1s CL spectra were also recorded to verify the presence of oxygen with Ga as shown in Figure S2, Supporting Information. It is observed that there was no chemical interaction between Ga and oxygen, suggesting the synthesis of GaN with the absence of any gallium oxy-nitride compound.…”
Section: Resultssupporting
confidence: 87%
“…The symmetric peaks at 393.2 and 397.4 eV indicate the presence of Ga Auger peaks and Ga-N bonding. 39,40 Figure 5d shows that the binding energy of O1s is centered at 531.6 eV, corresponding to oxygen bonding in non-stoichiometric oxides. 41 The above analysis demonstrates that the GON catalyst is non-stoichiometric and that the gallium atoms are bonded to oxygen and nitrogen in a compound state of Ga y O x N 1-x , which is in good agreement with the elemental analysis.…”
Section: Resultsmentioning
confidence: 99%
“…[25] Zhu et al, however, reported about the growth of a-Fe 2 O 3 @SnO 2 shuttle-like nanocomposites by a simple solvothermal method. [26] In an attempt, Chang et al [27] synthesized zigzag Ga 2 O 3 /GaN:O x heterogeneous nanowires and studied their gas sensing characteristics. As a further approach in this context, Park et al.…”
Section: Introductionmentioning
confidence: 99%